THE LEVEL OF CLIENT SATISFACTION WITH FOOD SERVED AT UPTD BAPELKESMAS DINAS KESEHATAN PROVINSI BALI - putu eka ananda kusuma dewi; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Satisfaction is a feeling of satisfaction after comparing performance with perceived expectations so that it can determine one aspect of quality in the administration of food. In this study there were 20 aspects of assessment of satisfaction levels. The type of research conducted is an observational study with a cross sectional design. The population of this study were all clients who conducted training at the UPTD BAPELKESMAS Dinas Kesehatan Provinsi Bali and 67 samples in this study were taken by purposive sampling method From 67 samples studied, most of them were satisfied with the food served at the UPTD BAPELKESMAS Dinas Kesehatan Provinsi Bali with an average satisfaction score of 93% which exceeded the standard of 80%. Based on the quadrant analysis that has been carried out, there are two aspects that are the top priority in the food served at UPTD BAPELKESMAS Dinas Kesehatan Provinsi Bali, namely the aroma of food and the appearance of the food presenter in dressing